PROGRESSIVE METHODS OF ASSESSING THE CAPITAL VALUE OF JOINT STOCK COMPANIES IN DEVELOPED COUNTRIES - Kgudoykulov, Khurshid (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article examines and analyzes the scientific and practical aspects of progressive methods for estimating the cost of capital of joint-stock companies in developed countries. It also describes methods commonly used in world practice, including methods of cost of equity and weighted average cost of capital. In addition to this , the methods used to analyze the cost of capital of joint-stock companies in Europe and the United States. In particular, the progressive capital valuation was used by the four largest accounting and consulting firms in the world.